2011
DOI: 10.3748/wjg.v17.i45.4993
|View full text |Cite
|
Sign up to set email alerts
|

Failed biliary cannulation: Clinical and technical outcomes after tertiary referral endoscopic retrograde cholangiopancreatography

Abstract: Referral to a high-volume center following unsuccessful ERCP is associated with high technical success, with a favorable complication rate, compared to routine ERCP procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 29 publications
1
21
0
2
Order By: Relevance
“…Furthermore, our success rate of 92%, although lower than desired, does not fall outside of the range reported in the literature for tertiary care centers, suggesting our method is an effective alternative. [13][14][15] On secondary analysis of our 32 unsuccessful procedures, there was no statistically significant difference found among all radiation parameters including FT, total radiation dose, DAP, and ED when compared with successful procedures. This suggests that these procedures were unsuccessful due to patient-related characteristics as opposed to the procedure-related use of fluoroscopic imaging.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, our success rate of 92%, although lower than desired, does not fall outside of the range reported in the literature for tertiary care centers, suggesting our method is an effective alternative. [13][14][15] On secondary analysis of our 32 unsuccessful procedures, there was no statistically significant difference found among all radiation parameters including FT, total radiation dose, DAP, and ED when compared with successful procedures. This suggests that these procedures were unsuccessful due to patient-related characteristics as opposed to the procedure-related use of fluoroscopic imaging.…”
Section: Discussionmentioning
confidence: 50%
“…Finally, referral to a high‐volume center following unsuccessful ERCP is effective. An Australian study demonstrated high success rates with a favorable adverse‐event rate compared to routine ERCP . In this prospective intention‐to‐treat analysis of 51 patients referred following recent unsuccessful ERCP, successful biliary cannulation was achieved in 100% of cases.…”
Section: Discussionmentioning
confidence: 93%
“…Biliary cannulation cannot be achieved because of special anatomical features, inflammatory processes, and periampullary diverticula. Some authors assert that low-risk patients undergoing failed ERCP without other complications could be successfully and safely treated by repeated ERCP if referred to an experienced high-volume endoscopy center [16]. However, repeated ERCP is bound to increase patient burden and the incidence of ERCP-related complications.…”
Section: Discussionmentioning
confidence: 98%